The emerging role of proactive therapy in atopic dermatitis and psoriasis - Pięta, Justyna; Chudzikowski, Marcel; Dudek, Patryk; Łuczak, Klaudia; Pawlik, Agnieszka; Prokopiuk, Agata; Prus, Joanna; Tabeau, Adrianna; Ulicka, Wiktoria; Sitarek, Hanna (Journal of Education, Health and Sport, 2025)
Proactive therapy represents an evolving approach in the long-term management of atopic dermatitis (AD) and psoriasis. Unlike reactive treatment, which targets active symptoms, proactive therapy involves the intermittent, low-dose application of anti-inflammatory agents to previously affected but clinically healed skin to prevent flare-ups. This strategy aims to reduce subclinical inflammation, extend remission periods, and improve patient quality of life. A growing body of evidence supports the efficacy of proactive treatment with topical corticosteroids, calcineurin inhibitors, and vitamin D analogues, demonstrating significant reductions in relapse rates and treatment costs. However, patient adherence remains a key challenge, necessitating structured follow-up and patient education initiatives. This review explores the pathophysiological basis of proactive therapy, its clinical applications, and current evidence supporting its role in AD and psoriasis management. Additionally, we discuss safety concerns, particularly regarding skin atrophy and hypothalamic-pituitary-adrenal axis suppression, and highlight emerging therapeutic options. While proactive therapy has demonstrated a favourable benefit-risk profile, further studies are needed to refine treatment protocols and expand its application to broader patient populations.